When school discipline meets children’s rights: A systematic literature review of tensions and conflicts in the international literature - Amy Hanna (International Journal of Educational Research Open, 2025)
In complex spaces such as schools, it is easy to see how children’s enjoyment of their rights may create rights conflicts where individual rights are claimed in a setting that is inherently collective. This presents tensions and oftentimes discord in decision-making in schools which are rarely debated as human rights concerns. This, perhaps, is because the ‘right to education’ is often understood as a right of access under article 28 of the Convention on the Rights of the Child (CRC), but not the features of a quality education enshrined in article 29 CRC. These features are most visible in an examination of school discipline policies which mediates the relationship between the State’s human rights obligations, duty bearing teachers, and students as rights-holders. This article presents the findings of a systematic literature review of 13 articles employing empirical, conceptual and doctrinal methodologies published between 2000–2024 which examine the human rights tensions and conflicts that arise from school discipline practice. The findings suggest that tensions and conflicts emerge between children’s education rights and school systems of rewards and sanctions, due process, and an absence of criteria for identifying, understanding and resolving human rights conflicts. I conclude by identifying several areas that require further empirical research.